Au-delà de la vocation artistique : un recrutement sexuellement différencié des candidat-e-s à une carrière de plasticien-ne ? - Mathilde Provansal (Éducation et Socialisation)
Women visual artists tend to disappear from the top of artistic rankings and continue to have a dominated position in the contemporary visual art world, even though about half of visual artists are women (Gouyon & Patureau, 2014), and art schools have been predominantly feminine for the past thirty years (Segré, 1993; Sotto, 2012). In this paper, we study the ways gender differences emerge in professional trajectories through the analysis of one particular moment that precedes the entrance into an artistic career, the admission to art school. Observing the admission oral exam to the École des Arts Plastiques reveals the criteria used by jury members to decide between those who can attempt an artistic career and outsiders. We show that women face gendered representations. This may affect early on their experience in art school and their future artistic career.